How to better identify patients at high risk of inappropriate shocks before S-ICD implantation: Results from a multicenter experience. (19th May 2022) - Ben Kilani, M; Jacon, P; Badenco, N; Marquie, C; Ollitrault, P; Behar, N; Khattar, P; Carabelli, A; Venier, S; Defaye, P
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Despite the recent improvements, inappropriate shocks (IAS) in patients implanted with subcutaneous implantable cardioverter-defibrillator (S-ICD) remain a challenge in "real-life" practice. The purpose of this study was to assess the preoperative predictive factors of IAS with the latest generation of S-ICD, with a particular focus on data obtained during the screening procedure. Methods: Between January 2017 and March 2020, 300 patients implanted with Generation 3 S-ICD system for primary and secondary prevention were included in this multicentric study. Follow-up (FU) of at least 6 months and preoperative screening procedure data were mandatory for all patients. Results: After a mean follow-up of 22.8 (±11.4) months, appropriate therapies occurred in 12.3% patients; while 26 patients (8.7%) experienced inappropriate therapies (incidence 4.9 per 100 patient-years). The total number of inappropriate shock episodes was 48; 9 patients experienced multiple episodes. Causes of IAS were: supraventricular arrhythmias (34.6%), cardiac (30.7%) and extra-cardiac noise oversensing (38.4%). In univariate analysis, availability of all 3 sensing vectors during preoperative screening significantly reduced inappropriate therapies occurrence (hazard ratio [HR], 0.32; 95% confidence interval [CI], 0.12-0.89, P=0.028). Clinical preoperative S-ICD inappropriate shocks predictors were: history of Supraventricular Tachycardia (SVT)(HR, 4.42; 95% CI, 1.45-13.47; P=0.009); overweight (BMI>25: HR, 1.93; 95% CI, 0.83-0.4.48; P=0.13); QRS duration (HR, 1.01; 95% CI, 0.1-1.03; P=0.14) and lower QRS/T wave ratio in lead I (for a threshold < 3: HR, 4.44; 95% CI, 1.88-10.48; P=0.001). By multivariate analysis, independent factors associated with IAS were: the availability of less than 3 sensing vectors during preoperative screening (p<0.05), a low QRS/T wave ratio in lead I (for a threshold <3; p<0.001), history of SVT (p<0.001) and overweight (BMI> 25; p<0.05). Conclusion: Automatic preoperative screening data is of high interest as a predictor of IAS with a quantitative value. ECG specificities in association with other clinical factors should be taken into consideration to identify patients at high risk for IAS.